The validity of dietary assessment in general practice. Issue 3 (1st March 1999) - Little, P; Barnett, J; Margetts, B; Kinmonth, A L; Gabbay, J; Thompson, R; Warm, D; Warwick, H; Wooton, S
Abstract : OBJECTIVE: To validate a range of dietary assessment instruments in general practice. METHODS: Using a randomised block design, brief assessment instruments and more complex conventional dietary assessment tools were compared with an accepted "relative" standard–a seven day weighed dietary record. The standard was checked using biomarkers, and by performing test-retest reliability in additional subjects (n = 29). OUTCOMES: Agreement with weighed record. Percentage agreement with weighed record, rank correlation from scatter plot, rank correlation from Bland-Altman plot. Reliability of the weighed record. SETTING: Practice nurse treatment room in a single suburban general practice. SUBJECTS: Patients with risk factors for cardiovascular disease (n = 61) or age/sex stratified general population group (n = 50). RESULTS: Brief self completion dietary assessment tools based on food groups caten during a week show reasonable agreement with the relative standard. For % energy from fat and saturated fat, non-starch polysaccharide, grams of fruit and vegetables and starchy foods consumed the range of agreement with the standard was: median % difference -6% to 12%, rank correlation 0.5 to 0.6. This agreement is of a similar order to the reliability of the weighed record, as good as or better than test standard agreement for more time consuming instruments, and compares favourably with research instruments validated in other settings. Under-reporting of energy intake was common (40%) and more likely if subjects were obese (body mass idex (BMI) > or = 30 60% under-reported; BMI < 30 29%, p < 0.001). CONCLUSION: Under-reporting of absolute energy intake is common, particularly among obese patients. Simple self assessment tools based on food groups, designed for practice nurse dietary assessment, show acceptable agreement with a standard, and suggest such tools are sufficiently accurate for clinical work, research, and possibly population dietary monitoring.